Deconstructing transphobic fallacies and unveiling the realities of transgender phenomenology in India: An empirical inquiry - Basu, Deblagno; Mukherjee, Soumik (Journal of Language, Literature, Social and Cultural Studies, 2023)
The community of the trans-gendered or the gender diverse or the gender nonbinary has been the cause of many debates in recent times over their claim of equal rights of existence in India. While several first world countries have taken or are in the course of taking adequate steps to ensure their inclusion among the general masses, India despite its long history of accommodation and tolerance has fallen behind. This is largely in lieu of the prevalent discourse classifying any form of sexuality and gender that does not conform to the heteronormative gender binary as unnatural and a product of westernisation. This paper endeavours to elucidate and scrutinize the Queer and specifically Trans elements embedded within Indian Mythologies, as manifested in the Veda, Purana, Dharma-Shastra, Kama-shastra, Natyashastra, and numerous other sacred texts. By doing so, it attempts to subvert the prevailing narrative that enforces their exclusion. In addition to that, it provides a comprehensive survey of gender fluidity as depicted in Indian mythologies and ancient texts, thereby illuminating the obscured heritage of progressive advancements in gender studies within the Indian context. Moreover, it underscores the contrived essence and artificial construct of the gender binary, while emphasizing the futility of steadfastly adhering to its purported "naturalness".